Postoperative outcome is affected by an intraoperative combination of each graft tension change pattern in a double-bundle anterior cruciate ligament reconstruction - Tomomasa Nakamura; Hideyuki Koga; Masafumi Horie; Toshifumi Watanabe; Kazuyoshi Yagishita; Ichiro Sekiya; Takeshi Muneta (Elsevier, 2016)
Background: The purpose of this study is to evaluate the intraoperative tension change pattern of each anteromedial (AM) graft and posterolateral (PL) graft and to investigate the optimal femoral tunnel position in double bundle (DB) anterior cruciate ligament reconstruction (ACLR) by comparing postoperative outcomes with each combination of graft tension change pattern. Methods: Eighty-four unilateral primary DB ACLR cases from 2006 to 2008 with a follow-up of 24 months or more were analysed. The tension change pattern of each AM and PL graft after graft fixation was recorded during DB ACLR, and divided into over-the-top (OTT; tension at 0° > 120°) and reverse OTT (graft tension at 0° < 120°) pattern. The combinations of these patterns were then categorized into four groups and the postoperative results were analysed. The femoral tunnel position was measured by a modified quadrant method. The relationship between the femoral tunnel position and the tension change pattern of each graft was evaluated. Results: The cases that presented reverse tension change pattern of native anterior cruciate ligament (ACL) performed most poorly in postoperative knee laxity among the four groups. In this group, the femoral tunnel of the AM bundle was placed significantly higher in flexion. Conclusion: This study suggests that the least effective method for knee stability recovery is for the ACL to be reconstructed with the reverse tension change to the native ACL. It is necessary to refrain from placing the femoral tunnel for the AM bundle in a high position in knee flexion in DB ACLR.